Víctor Cortezo y los sacripantes del Partido. Notas a un poema de Luis Cernuda - Sánchez Rodríguez, Alfonso (Huarte de San Juan. Filología y Didáctica de la Lengua, 2012)
We analyze the poem by Luis Cernuda “Amigos: Victor Cortezo” written in 1961. In this poem there is a key event that took place in Valencia in 1937. This is the arrest of Victor Cortezo and his stay in the communist “checa” (unofficial prison) of Germanias, another sign of terror as a method applied during the Spanish Civil War.
Keywords: Spanish Generation of 27; Luis Cernuda; Víctor Cortezo; Spanish Civil War; communist unofficial prison